Câmara Cascudo interprete do Brasil: Portraits of a brazilian diet (Research, Society and Development, 2020)
This article aims to comprehend Câmara Cascudo as one of the thinkers who contributed to the realization of a reading on the Thought of Brazil. For this understanding, we took as a base of investigation his book History of Food in Brazil, which is a peculiar production present in the corpus of his work, he sought in Brazilian culinary ways to think about a cultural heritage inherited from the three ethnicities that integrated and gave rise to the country's racial composition It is a careful investigation, through a historical bias, with the objective of "showing the antiquity" of food predilections, with a focus on returning to the origins of the three ethnicities that form Brazil, giving the work a tone of nationality study. Cascudo intended to seek the “roots” of the formation of our nationality from a theme present intensely in Brazilian society which is the composition of the diet Brazilian food, following a detailed investigation present in the long centuries of mixing of the races creator of Brazil, studying the changes that have been passed over time. Therefore, it is a book that works with nationality, seeking in the dietary formation of the Brazilian people what resembles us and what differs from the nations of origin, whose source of research is the popular food, and for her the author stressed the potential of the national taste, enabling the debates on ethnicity, colonization and cultural heritage.